Produktivitas Tenaga Kerja Keluarga Pada Usaha Sapi Bali Terintegrasi Perkebunan Kelapa Sawit Di Kecamatan Wiwirano Kabupaten Konawe Utara - Sani, La Ode Arsad; Munadi, Laode Muh.; Abadi, Musram; Alfiansyah, Alfiansyah; Pagala, Muhammad Amrullah; Sandiah, Natsir (Jurnal Social Economic of Agriculture, 2021)
The development of beef cattle farms can be done through an integrated system and the involvement of family labor. The objective of this study is to know the family labor productivity in the integrated Bali cattle business and palm oil plantations in Wiwirano District, North Konawe Regency. The research material is breeders in the District of Wiwirano who carry out the integration efforts of Bali cattle and palm oil, As many as 4 villages in Wiwirano district, that integrated the Bali cattle and oil palm were determined by stratified sampling. 60 respondents from 4 villages were selected using simple random sampling. The average allocation of family labor in the Bali cattle business reaches 5,635 hours/day or 0,653 HOK/day. While the allocation of family labor in the palm oil business reaches 10,121 hours/day or 1,151 HOK. The technical productivity of the Bali cattle business is 4,72 ST/HOK and economic productivity is Rp 83.983,43/HOK. While the technical productivity of the oil palm plantation business is 133,69 kg/HOK and economic productivity is Rp 120.772,75/HOK.Keywords: Labor, Bali Cattle, Palm Oil.